Numerical Simulation Study on the Effect of CO2 Laser on the Plasma Behavior - Tawfiq, Esam Ahmed (Al-Nahrain Journal of Science, 2018)
The present work, the plasma is simulated using particle model under the action of CO2 laser by using power density 1015W per centemete2.The behavior of the plasma is studied in three electron density regions below the critical density. The time history of the total energy, kinetic energy, and the drift energy are studied at 0.9ncr, 0.95ncr, and 0.99ncr. The results indicated that the total energy of the system slightly increases at the first time steps after that time a rapid increase in the energy are observed. The time evolution of the kinetic energy is studied, the results show that the plasma heating increases rapidly due to the acceleration of the plasma particles by the laser light. In this work the time history of the drift energy is plotted at each time step of the run.